Face Recognition Using Principal Component Analysis Method - Mahale, Neelam; Nagmode, Manoj S; Ghatol, Prajakta S (International Journal of Computer Sciences and Engineering, 2014)
In this paper the method of Face Recognition is presented. Now a day the need of security is increasing. Many methods are using for maintaining the security like as credit cards, pin numbers, smart cards etc. But some times it fails. This paper presents a Face Recognition method using Principal Component Analysis. This method applies on both data base image and input image. By the use of PCA the system finds the Eigen values, Eigen vector and Euclidian distance. After comparing from database it declares the matches.